2018
DOI: 10.5455/msm.2018.30.58-61
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Periodontitis in Patients Undergoing Hemodialysis: a Case Control Study

Abstract: Objectives:To assess the prevalence of periodontal disease among patients undergoing renal dialysis.Methods:Sixty hemodialysis patients (30 males, 30 females) with a mean age of 44.4±9.5 years comprised the study group. Periodontal parameters such as plaque index (PI), bleeding on probing (BOP), probing pocket depth (PPD) and clinical attachment level (CAL) were measured in these patients and 60 age and sex-matched control subjects. The data was tabulated and analyzed.Results:The mean duration of dialysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Data on oral health parameters of CKD patients have been controversial. Some studies reported no difference in PI between patients with ESRD and controls (12-15), whereas others showed higher average plaque index in ESRD patients on dialysis (13,21,22). Several factors may have contributed to these differences, including inadequate adjusting for some confounding variables.…”
Section: Discussionmentioning
confidence: 99%
“…Data on oral health parameters of CKD patients have been controversial. Some studies reported no difference in PI between patients with ESRD and controls (12-15), whereas others showed higher average plaque index in ESRD patients on dialysis (13,21,22). Several factors may have contributed to these differences, including inadequate adjusting for some confounding variables.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence supports ESRD could make periodontal microbial community different from that of those without ESRD [ 44 ]. The interplay between microbial agent and the adjacent periodontal tissues often increases gingival inflammation and releases biologically active substances [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have suggested that correct diagnosis and appropriate treatment of periodontal disease are important not only to the improvement of oral infection and inflammation, but also to maintain systemic health in patients receiving dialysis, and that managing oral health can effectively prolong survival [15,16,17,23,41,61,70]. In fact, brushing the teeth twice daily led to a reduced chance of developing periodontal diseases than brushing once daily, and it was identified as an independent factor [36].…”
Section: Management Of Periodontal Diseasementioning
confidence: 99%
“…Even if such reports are excluded, many studies have reported that over half of HD patients exhibit periodontitis [11,12,13,14]. Furthermore, most periodontal parameters in HD patients were reported to be significantly higher than those in age-matched control subjects and healthy individuals [15,16,17]. Thus, many investigators have shown that periodontal disease is an important issue in patients with PD and HD.…”
Section: Introductionmentioning
confidence: 99%